[OP.3B.01] VALIDATION OF FRAMINGHAM AND SCORE IN 30560 PATIENTS WITH HYPERTENSION. (September 2017) - Le, H.; Marchant, I.; Subtil, F.; Boissel, J.; Gueyffier, F.
Abstract : Objective: To validate the Framingham and SCORE predictors for cardiovascular death and death from coronary heart diseases in 30560 individuals with hypertension. Figure. No caption available. Design and method: Individual patient data was collected from seven randomized controlled trials (INDANA database and DIABHYCAR trial). We used the Framingham and SCORE equations to estimate the risks of cardiovascular death and death from coronary heart diseases of each patient. Predicted values were compared with observed ones in function of gender and age range. Results: Both Framingham and SCORE seemed to work best in men aged 55–65. For men older than 65, both overestimated dramatically, particularly SCORE. For women older than 55, both predictors overestimated dramatically, particularly Framingham on the contrary for both outcomes. For women and men younger than 55, Framingham and SCORE slightly underestimated their risks (Fig. 1). Conclusions: In general, Framingham and SCORE appear to better predict risks of cardiovascular death and of death from coronary heart diseases in younger people in our database (<55 years old). On older subjects, both overestimated and in contrary tendency for men and women. These overestimations may due to shorter mean duration of follow-up of studied population (mean 4.96 years, max 11.87 years) vs. 10-year-risk predicted.